PERBEDAAN TINGKAT KECEMASAN ANAK USIA PRASEKOLAH SEBELUM DAN SESUDAH DILAKUKAN TERAPI BERMAIN PADA ANAK YANG MENJALANI HOSPITALISASI DI RUANG ANAK RUMAH SAKIT UMUM (RSUD) TANGERANG SELATAN TAHUN 2016 - Rahayu Susanti; Dewa Ayu Sri Saraswati (Jurnal Kesehatan STIKes IMC Bintaro, 2017)
Preliminary Hospitalization can cause anxiety to preschool children due to separation, lossing of control, injury and pain of body. Play therapy aims to minimize anxiety in preschool children during hospitalization. The purpose of this study was to to analyze the effect of play therapy toward Anxiety Level on Preschool Age Children Hospitalization In Mawar’s Room General Hospital on South Tangerang. This research used design approach quasy experiment with non equivalent control group design. Sampling technique used purposive sampling with a sample size of 34 respondents divided into 2 goups. Research was conducted in Mawar’s Room General Hospital on South Tangerang. Research instrument used anxiety questionnaire modification HAR’S.Research result. Data were analyzed using data normality and t-test. Based on t test results obtained in this study is the p-value p = 0.0001 <α = 0.05. Conclusion. It can be concluded that there was an effect of Play Therapy for Anxiety Level on Preschool Age Children With Hospitalization In Mawar’s Room General Hospital on South Tangerang. It is sugested that nurses can provide play therapy to minimize or remove anxiety to preschool children during hospitalization.